HUBUNGAN SOCIAL COMPARISON DENGAN SELF-ESTEEM PADA REMAJA PENGGUNA INSTAGRAM DI KOTA MANADO - Mirando Abram Pakasi; Dewita Karema Sarajar (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Instagram is one of the most widely used social media platforms among adolescents, and its use is closely associated with activities of comparing oneself to other users. This phenomenon prompted the researcher to examine the relationship between social comparison and self-esteem among adolescent Instagram users in Manado City. This study employed a quantitative approach with a correlational design. A total of 151 adolescent participants aged 13–18 years were selected using purposive sampling. Data were collected using the Iowa Netherlands Comparison Orientation Measure (INCOM) to measure social comparison and the Self-Liking and Self-Competence Scale Revised (SLCS-R) to measure self-esteem. Data analysis was conducted using Spearman's rho correlation test. The results showed a correlation coefficient of −0.664 with a significance value of 0.000 (p < 0.01), indicating a significant negative relationship with strong magnitude between social comparison and self-esteem. These findings suggest that adolescents with higher tendencies toward social comparison tend to have lower self-esteem. The results of this study can serve as a basis for developing psychological interventions aimed at helping adolescents manage their tendency to compare themselves on social media in order to maintain their mental health. ABSTRAK Instagram merupakan salah satu platform media sosial yang paling banyak digunakan oleh remaja, dan penggunaannya tidak lepas dari aktivitas membandingkan diri dengan pengguna lain. Fenomena ini mendorong peneliti untuk mengkaji hubungan antara social comparison dan self-esteem pada remaja pengguna Instagram di Kota Manado. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Sebanyak 151 partisipan remaja berusia 13–18 tahun dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan Iowa Netherlands Comparison Orientation Measure (INCOM) untuk mengukur social comparison dan Self-Liking and Self-Competence Scale Revised (SLCS-R) untuk mengukur self-esteem. Analisis data menggunakan uji korelasi Spearman's rho. Hasil penelitian menunjukkan koefisien korelasi sebesar -0,664 dengan nilai signifikansi 0,000 (p < 0,01), yang berarti terdapat hubungan negatif yang signifikan dengan kekuatan kuat antara social comparison dan self-esteem. Temuan ini mengindikasikan bahwa social comparison dan self-esteem memiliki keterkaitan yang bermakna secara psikologis, di mana keduanya bergerak dalam arah yang berlawanan pada remaja pengguna Instagram di Kota Manado. Hasil penelitian ini dapat menjadi dasar bagi pengembangan intervensi psikologis yang bertujuan membantu remaja mengelola kecenderungan membandingkan diri di media sosial guna menjaga kesehatan mental mereka.